Towards SCADA Threat Intelligence based on Intrusion Detection Systems - A Short Review - Qassim Q.S.; Jamil N.; Mahdi M.N.; Abdul Rahim A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer crime; Intrusion detection; Catastrophic consequences; Defence mechanisms; Detection methods; Intrusion Detection Systems; Malicious activities; Scada networks; Stealth attacks; Supervisory control and dataacquisition systems (SCADA); SCADA systems